2010
DOI: 10.1017/s1368980010002673
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of increasing waist circumference in an Australian population

Abstract: Objective: To identify predictors of increasing waist circumference (WC) over a 5-year period in a contemporary population of Australian adults. Design: Longitudinal national cohort of adults participating in the Australian Diabetes, Obesity and Lifestyle Study (AusDiab). Settings: Australian adults in 2000 and 2005. Subjects: A total of 2521 men and 2726 women aged $25 years at baseline who participated in AusDiab and provided anthropometric measurements at baseline (1999)(2000) and follow-up (2005). Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
7
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…27 Our findings are in agreement with such a pattern. However, it is noteworthy that our data suggest that women continued to gain weight and WC until an older age compared to men, a finding which corresponds with earlier longitudinal studies 28,29 and may be partly explained by changes due to the menopausal transition in women in this age group. 30 Age-related weight gain has been shown to occur even among physically active people.…”
Section: Discussionsupporting
confidence: 90%
“…27 Our findings are in agreement with such a pattern. However, it is noteworthy that our data suggest that women continued to gain weight and WC until an older age compared to men, a finding which corresponds with earlier longitudinal studies 28,29 and may be partly explained by changes due to the menopausal transition in women in this age group. 30 Age-related weight gain has been shown to occur even among physically active people.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has also shown that diet quality is associated with risk of type 2 diabetes in women, independent of central adiposity (Fung et al, 2007). Poor diet quality has been shown to be the strongest behavioural predictor of gain in waist circumference over five years (Walls et al, 2011). Taken together, this study further highlights that improving diet quality in line with national dietary guidelines is an important public health target for improving glycemic health and preventing obesity, particularly for women.…”
Section: Discussionsupporting
confidence: 58%
“…While consensus is forming around the role of specific dietary elements and markers of physical activity and inactivity associated with increased weight gain (1)(2)(3) , few studies have analysed predictors of increasing waist circumference (4)(5)(6)(7) and the majority of these have focused solely on dietary factors.…”
mentioning
confidence: 99%
“…Further, there is evidence that waist circumference is increasing at a faster rate than BMI (7,9) , suggesting that there may be differential drivers of BMI and waist circumference. A recent analysis of cohorts in the European Prospective Investigation into Cancer and Nutrition suggested that specific dietary elements may predict changes in waist circumference independent of changes in BMI (5) .…”
mentioning
confidence: 99%